2018
DOI: 10.3727/096504017x14941825760362
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone Suppresses Arecoline-Induced EpithelialMesenchymal Transition in Oral Submucous Fibrosis by Epigenetically Reactivating the p53 Pathway

Abstract: Oral submucous fibrosis (OSF) induced by chewing of the areca nut has been considered to be a precancerous lesion with a high probability of developing oral squamous cell carcinoma. Tanshinone (TSN) is the main component extracted from , a traditional Chinese medicine, which was found to have diverse pharmacological effects, such as anti-inflammatory and antitumor. In the current study, we aimed to identify the inhibitory effects and the underlying mechanism of TSN on OSF progress. We found that treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…This material consists of dihydrotanshinone I, tanshinone I, and tanshinone IIA and has anti-inflammatory and antioxidant activity. Tanshinone epigenetically interacts with the p53 pathway which is downregulated in OSF [135]. Salvianolic acid B is also extracted from Salvia miltiorrhiza.…”
Section: Natural Compound Remediesmentioning
confidence: 99%
See 1 more Smart Citation
“…This material consists of dihydrotanshinone I, tanshinone I, and tanshinone IIA and has anti-inflammatory and antioxidant activity. Tanshinone epigenetically interacts with the p53 pathway which is downregulated in OSF [135]. Salvianolic acid B is also extracted from Salvia miltiorrhiza.…”
Section: Natural Compound Remediesmentioning
confidence: 99%
“…Decrease α-SMA and fibronectin and type 1 collagen A1 expression Inhibit myofibroblast activity (migration and contraction) [75] Glabridin Decrease α-SMA, type I collagen, and TGF-β Inhibit myofibroblast activity (migration and contraction) [131] Asiatic acid Inhibit TGF-β1, collagen 1 type 2, and collagen 3 type 1 [134] Tanshinone reactivate p53 [135] Salvianolic acid B with Triamcinolone acetonide…”
Section: Butylidenephthalidementioning
confidence: 99%
“…Arecoline treatment of oral mucosal fibroblasts resulted in reduction of p53 and its related downstream molecules p21, Bax, and p53 upregulated modulator of apoptosis (PUMA). [7] Arecoline promoted hypermethylation of promoter of p53, which was reversed by TSN. In G1-S phase cell cycle, the repair of damaged DNA is facilitated by p53 protein.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The authors suggested that TSN could be of help in intervention against OSMF and OSCC. [7] Ding et al investigated the radiosensitizing effects of TIIA on human OSCC. The authors observed that TIIA significantly sensitized SCC090 OSCC cells to radiation through enhanced reactive oxygen species generation and autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation